AS IMPLICAÇÕES DO PROCESSO DE RESISTÊNCIA QUILOMBOLA NO ESPAÇO ESCOLAR NO MUNICÍPIO DE RESERVA DO IGUAÇU - Raimondo, Marilene Aparecida Soares Uchak (2017)
This study highlights the possible learning difficulties presented by maroon students in the schooling process. Our objective is to verify the implications of the presence of maroon students in the process of cultural resistance at Izabel F. Siqueira High School, located in the municipality of Reserva do Iguaçu, Paraná. We use educational ethnography as our methodology in an attempt to understand how the customs and traditions of a human group occur, in this case, the Maroon Community. We even try to elucidate how the learning dynamics of these students occur, verifying if there is denial or silencing of the Afro-Brazilian culture and what are the implications in the teaching and learning process of maroon students. As a method of document analysis we carry out bibliographic research and the compilation of documents on historical aspects and students enrollment, considering the school data as the main source. We also consider the training course of the Núcleo de Estudos Ameríndios e Africanos (NEAA) offered by UNICENTRO University, as a basis for research and community outreach. The research was carried out at the Izabel F. Siqueira High School through a training course and visits to the Maroon Community. With the present study we were able to observe that the Maroon Community obtained some considerable achievements: the construction of a barracks, improvement of the roads that give access to the school, division of the land of a new area received by them and the beginning of the process for the construction of a new school within the Maroon Community area. On the learning difficulties presented by students we evidenced that there were also significant changes.